PENGARUH VOLATILITAS HARGA MINYAK TERHADAP PEREKONOMIAN - Ruth Meilianna (Bina Ekonomi, 2017)
This study discusses the impact oil price volatility on macroeconomic variables, in particular economic growth, inflation, and output gap. Data used in this study are the quarterly standard deviation of oil spot price of West Texas Intermediate (WTI), and macroeconomic variables of 19 countries in the world for the period of time of 1997.Q1 – 2013.Q4. This study uses Least Square Dummy Variable (LSDV) equation that is converted into Fixed Effect Model (FEM). This study concludes that oil price volatility influences inflation, output gap, and economic growth. Through inflation, oil price volatility affects the interest rate. Moreover, estimation using equation system also shows the interconnection among macroeconomic variables and how oil price volatility could influence other variables.Keywords: oil price volatility, macroeconomic variables, inflation, interest rate